(untitled) (Medical Forum Monthly, 2024)
Objective: The objective of this study was to determine the pattern of presentation of Gall Bladder Carcinoma and Surgical Management in South Punjab. Study Design: Prospective study. Place and Duration of Study: This study was conducted Surgical Department of District Headquarters & Teaching Hospital, D.G. Khan Medical College, Dera Ghazi Khan from July, 2018 to July 2019. Materials and Methods: Total of 25 patients of Carcinama of Gall Bladder were treated within period of one year. There were 4 males and 21 females with male to female ratio 1:5. Ages of patients ranges from 38 to 72 years with max. incidence in 5th decade. Presenting features were pain in right hypochondrium in 88%, nausea & vomiting in 60%, weight loss in 40%, Jaundice in 28%, mass in right hypochondrium in 20%, pruritis in 20%, fever in 12%, anorexia in 12% and ascites in 4% of cases. The investigations done in these patients were USG abdomen, CT abdomen and other basic investigations. Results: All the patients were operated and divided into three groups. (i) Nevin staging system I & II. (ii) Nevin III Patients with stage IV & V. Simple cholecystectomy was done in 10 patients of group I. extended cholecystectomy was done in two patients of group II. Laparatomy and biopsy of mass with palliative surgery and bile drainage in 13 patients of group III. Adenocarcinoma was diagnosed in 88% (22 patients) and squamous cell carcinoma in 8% (2 patients) was diagnosed on histopathological study. Conclusion: The study concludes that gallstones are most important factor causing the carcinoma. So malignancy should be suspected in any long standing cases of cholelithiasis. So early cholecystectomy should be recommended in gall stone cases.